Public relations : a values-driven approach : cases edition - Guth, David W., ....-; Marsh, Charles, ....- (Boston [et al.] : Pearson, 2007)
Public Relations: A Values-Driven Approach is the articulation of a philosophy the authors call values-driven public relations. VPR combines the traditional four-step process of public relations with a focus on values -- those of practitioners, their organization, targeted publics, the profession, and society. Now in its third edition, Public Relations: A Values-Driven Approach prepares future practitioners for a world in which they and the organizations they will represent are increasingly held accountable. The authors of the book also understand that public relations did not develop, nor is it practiced, in a vacuum. Issues challenging 21st century practitioners are discussed within a broad social context. The result is a book that provides its readers with a clearer understanding of the so-called "real world" they are about to enter. There are chapters focusing on the hottest issues confronting the profession, including ethics, law, cross-cultural communication, crisis communication
And new technologies. A major goal of the book is to strengthen students' problem-solving skills. To that end, real-life case studies, as well as realistic scenarios, are included in each chapter. The book also introduces a variety of processes that guide students through the public relations process and ethical decision making. The book includes numerous learning aids and interesting sidebars designed to engage the reader. Each chapter features a memo to student from one of today's leading practitioners. The third edition brings its readers some of the latest research and developments in the exciting field of public relations. It also focuses on the tragic events of September 11, 2001, that have changed our lives in so many ways. Using the conversational style of writing favored by today's students, Public Relations: A Values-Driven Approach takes its readers on a journey of discovery that focuses on who we are, where we want to go, and the values we will hold in getting there.
Keywords: Public relations